OPTIMALISASI MEDIA SOSIAL TIKTOK UNTUK BISNIS ONLINE IBU RUMAH TANGGA DI MASA PANDEMI COVID 19 - Nur Huda; Kurnia Setyoningrum; Sokhikhatul Mawadah; Nihayah, Ana Zahrotun (LPPM ITB AAS Indonesia Surakarta, 2025)
Tiktok is one of social media which describe only used for dancing and entertainment, and then now Tiktok not only used for that but can be used as a selling medium. The Tiktok application can be linked to the tiktok seller application or the tiktok shop so that personal accounts can also be used to sell. During the pandemic, housewives can use tiktok to increase their income. Housewives who have or don't have an online business can use tiktok social media to increase their income. Through community service work, we organize training, practice and mentoring for housewives to do business online using social media Tiktok. The service starts from providing technical guidance, assisting practice as well as monitoring and evaluation. The housewives we accompany are able to link their personal accounts to the seller's tiktok account, can fill in all the necessary data and can add a yellow basket to the uploaded video. If the personal tiktok account already has a yellow basket, then this community service is called successful. Furthermore, housewives who take part in this optimization activity can sell using their tiktok account. Although successful, there are still many obstacles faced including: the number of followers is still small, product categories are still few to be inputted and the quality of the video still needs a lot of improvement in order to be watched or get a lot of views.